Integration of Evora-InovGrid Smartmeters in a Consumer’s SCADA System - Pereira, Rita (2016)
This paper develops an energy management system with smart meters integration for electricity consumers in a smart grid context. The integration of a distributor owned smart meter from the main Portuguese electricity distributor – EDP - is developed. The smart meter is connected to a common PC, that runs the Matlab Software and communicates to the SCADA system (Supervisory Control And Data Acquisition) using the OPC Protocol. The SCADA system supervises an industrial network of Programmable Logic Controllers (PLC). The developed control strategy implements a hierarchical cascade controller where inner loops are performed by local PLCs and the outer loop is managed by a centralized SCADA system, which interacts with the entire local PLC network.